2009
DOI: 10.1021/la900394z
|View full text |Cite
|
Sign up to set email alerts
|

Accurately Tuning the Charge on Giant Polyoxometalate Type Keplerates through Stoichiometric Interaction with Cationic Surfactants

Abstract: We report an approach of exploring the interaction between cationic surfactants and a type of structurally well-defined, spherical "Keplerate" polyoxometalate (POM) macroanionic molecular clusters, {Mo72V30}, in aqueous solution. The effectiveness of the interaction can be determined by monitoring the size change of the "blackberry" supramolecular structures formed by the self-assembly of {Mo72V30} macroions, which is determined by the effective charge density on the macroions. Long-chain surfactants (CTAB and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 39 publications
1
28
0
1
Order By: Relevance
“…48 Liu, Kegel, Müller, and coworkers investigated that the size of blackberry assemblies is highly controllable either by optimizing the solvent contents or by tuning the charge density of the POM giant anion. [55][56][57][58][59] Covalent grafting of an organic group onto POM clusters has drawn tremendous attention in the last few years. Many researchers including Wei's, Gouzerh's, Cronin's, Peng's, Hill's and Bonchio's research groups, among others, have reported several covalently modified POM hybrid clusters.…”
Section: Introductionmentioning
confidence: 99%
“…48 Liu, Kegel, Müller, and coworkers investigated that the size of blackberry assemblies is highly controllable either by optimizing the solvent contents or by tuning the charge density of the POM giant anion. [55][56][57][58][59] Covalent grafting of an organic group onto POM clusters has drawn tremendous attention in the last few years. Many researchers including Wei's, Gouzerh's, Cronin's, Peng's, Hill's and Bonchio's research groups, among others, have reported several covalently modified POM hybrid clusters.…”
Section: Introductionmentioning
confidence: 99%
“…When CTAB was added to {Mo 72 V 30 }, stable supramolecular structures formed (Note: from current point of view, the “blackberry” structure we suggested previously could also be vesicles formed by amphiphilic surfactant–clusters complexes.) even up to the CTAB/{Mo 72 V 30 } molar ratio of 10 (Table S1, Supporting Information) and no inhomogeneous distribution of cationic surfactants was observed. Given that all other conditions are similar, the most probable reason that leads to the different behaviors of {Mo 72 V 30 } and U 60 clusters would be the surface charge density.…”
Section: Figurementioning
confidence: 98%
“…Moreover, the model predicts that at constant e, i.e., in the same solvent, the size of the shell R Ã / r À2=3 . If surfactant is used to regulate the charges on the POMs [14], then a model describing adsorption of surfactant on the chargeable groups of the POM may be needed to relate the charge density with the concentration of the surfactant. For the condition of constant charge density to be valid, the maximum permissible value of surface potential should satisfy the following condition:…”
Section: Theorymentioning
confidence: 99%
“…Recently Kistler et al [14] investigated the effect of addition of surfactants to {Mo 72 V 30 } POMs and reported the size of the shell as a function of concentration of surfactant. They used cationic surfactants such as cetyltrimethylammonium bromide (CTAB), cetyltrimethyltetradecylammonium chloride (CTAT), octyltrimethylammonium bromide (DTAB) and octyltrimethylammonium bromide (OTAB).…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation